Multicultural Personality pada Toleransi Mahasiswa - Azmi, Rafida; Kumala, Anisia (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2019)
AbstractIndonesia is a country that consists of several islands and one of the countries that has many diverse tribes and cultures. Successes and participation that are agreed upon are responded to, responded to and managed properly and agreed with a positive personality will draw attention to the benefits that can be received. Personalities that support personal freedom as well as others who represent cultures or backgrounds that differ from principles, culture, social and religion are multicultural personalities. Tolerance is someone who accepts and values, opposes, and has a lifestyle that is different from oneself because he disagrees with it. The purpose of this study was to determine the presence or absence of significant differences between Multicultural Personalities on student spending. This research method uses quantitative research methods. The population in this study were students and the sample in question was 167 students surviving 17-28 years. The research subjects were taken randomly or Non Probability Sampling and using Accidental Sampling techniques. The scale used is the Multicultural Personality Questionnare (MPQ) as a measure of Multicultural Persnality consisting of 40 items with (alpha Î± efficiency = 0.736) and Tolerance Index (TI) as a measuring tool consisting of 22 items with (alpha Î± efficiency = 0.667 ). Data analysis in this study used a regression technique with SPSS. Based on the regression results, it is recognized the value of R square to analyze the regression on the influence of Multicultural Personality on Tolerance of 0.103 with a value of 32 0.322 and a significant value of 0,000 which means to show a personality that is Multicultural capable of change in students. The contribution of multicultural personality is 10.3% to the rest of the allocation with other factors.AbstrakIndonesia merupakan sebuah negara yang terdiri dari beberapa pulau dan salah satu negara yang memiliki banyak suku dan budaya yang beranekaragam. Keberagaman dan keanekaragaman apabila disikapi, ditanggapi dan dikelola secara benar dan dipandang dengan keperibadian yang positif maka akan menimbulkan adanya perilaku toleransi. Kepribadian yang mampu menghargai diri sendiri serta orang lain yang berasal dari budaya atau latar yang berbeda baik secara prinsip, budaya, sosial dan agama adalah kepribadian multikultural. Toleransi adalah seseorang yangÂ menerima dan menghormati, terhadap pendapat, perilaku dan gaya hidup yang berbeda dengan diri sendiri meskipun seseorang tersebut tidak setuju dengan hal itu. Tujuan penelitian ini untuk mengetahui ada atau tidak adanya pengaruh yang signifikan antara Multicultural Personality terhadap toleransi pada mahasiswa. Metode penelitian ini mengguanakan metode penelitian kuantitatif. populasi dalam penelitian ini adalah mahasiswa dan dengan sampel yang berjumlah yaitu 167 mahasiswa berusia 17-28 tahun. Subjek penelitian diambil secara acak atau Non Probability Sampling dan menggunakan teknik Accidental Sampling. Adapun skala yang digunakan adalah Multicultural Personality Questionnare (MPQ) sebagai alat ukur Multicultural Persnality yang terdiri dari 40 item dengan (kefisien alpha Î± = 0,736) dan The Tolerance Index (TI) sebagai alat ukur toleransi yang terdir dari 22 item dengan (kefisien alpha Î± = 0,667). Analisis data pada penelitian ini menggunakan teknik regresi dengan SPSS. Berdasarkan hasil regresi, diketahui nilai R square untuk analisa regresi pada pengaruh Kepribadian Multikultural terhadap Toleransi sebesar 0,103 dengan nilai